2008
DOI: 10.1007/s10911-008-9068-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prolactin Receptor Levels and Activity in Breast Cancer

Abstract: From its traditional identity as a hormone involved in growth and differentiation of mammary epithelium and in lactation, to having a pertinent role in the development of mammary carcinoma, the peptide hormone/cytokine prolactin (PRL) has emerged as a versatile signaling molecule. There has been significant progress in our understanding of the fine working of PRL in the past several years. Notably, much effort has been concentrated on the mediator of PRL action, namely, the prolactin receptor (PRLr). The causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 94 publications
4
51
0
3
Order By: Relevance
“…In previous studies, down-regulation of the PRLr resulted in slower cell growth in normal growth conditions. 21 Similarly, siRNA targeted against the PRLr inhibited cell proliferation ( Figure 3F). Taken as a whole, these results suggested that the PRLr, and specifically the Microarray values were analyzed in Partek Genomics Suite.…”
Section: Prlr Function In Breast Cancermentioning
confidence: 89%
“…In previous studies, down-regulation of the PRLr resulted in slower cell growth in normal growth conditions. 21 Similarly, siRNA targeted against the PRLr inhibited cell proliferation ( Figure 3F). Taken as a whole, these results suggested that the PRLr, and specifically the Microarray values were analyzed in Partek Genomics Suite.…”
Section: Prlr Function In Breast Cancermentioning
confidence: 89%
“…It has a three-domain organization: an extracellular ligand-binding domain, which confers specificity, a short transmembrane domain, and an ICD (Swaminathan et al 2008, Clevenger et al 2009). In addition to the most abundant 80 kDa long isoform, shorter variants that couple to different signaling pathways are detectable in breast cancer.…”
Section: Characteristics Of Prl and Prlrmentioning
confidence: 99%
“…Whereas estrogens can bind to several classical (ERa and ERb) and nonclassical (G protein-coupled receptor 30, GPR30) receptors (Manavathi & Kumar 2006), there is only one receptor (PRLR) for PRL, albeit it exists in several isoforms which couple to different signaling pathways (Swaminathan et al 2008). Yet, there is crosstalk between the two hormones, with PRL increasing the expression and phosphorylation of ERa (Carver et al 2009), and E 2 inducing the transcription of both PRL (Duan et al 2008) and the PRLR (Swaminathan et al 2008). Such interactions can result in augmentation, or synergism, between the two hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Les régulations de la quantité de récepteurs de la PRL et de leur activité de modulation des signalisations intracellulaires, ainsi que de la PRL endogène, pourraient être des facteurs de progression des tumeurs mammaires et prostatiques [2,33,34]. Des effets combinés des formes PRL 23 kDa et 16K, cette dernière pouvant avoir une activité antitumorale, ont été envisagés dans la croissance de tumeurs de la prostate [35].…”
Section: Les Pathologies Liées à La Prl Et à Sa Forme 16kunclassified